The Meeting of Islam and Adat: Exploring the Religiosity of Bajau Samah Community in Kotabaru - Nurbayani, Etty; Husin, M. Said (Center for Research and Development of Religious Literature and Heritage, 2024)
The Bajau people, an indigenous group residing along the shores of the archipelago, primarily in Borneo and Celebes Islands, perceive their religiosity differently from other land-based or maritime societies. This paper aims to explore the dimensions of religiosity among the Bajau Samah in Kotabaru, South Kalimantan. This ethnographic research involved researchers participating in the community’s religious-cultural activities, such as the Ma’dupa and Menyurung rituals. The findings reveal that the Bajau Samah are inseparable from their sea and ancestors. These elements are not only their sources of livelihood and wisdom but also crucial ‘figures’ that shape their religiosity. Their experiences and thought processes regarding the sea and their ancestors manifest in various forms: religious feeling, religious belief, religious knowledge, religious practice, and religious effect. This study argues that while adat (customary law) and religion (Islam) are distinct domains, they collectively constitute the religiosity of the Bajau Samah, as evidenced in Kotabaru.